Psychological and behavioural patterns of stigma among patients with type 2 diabetes: a cross-sectional study - Kato, Asuka (BMJ Open, 2017)
OBJECTIVES: The aim of this study was to test the psychological and behavioural patterns of stigma (self-esteem and social participation) and their relationship to self-stigma, patient activation for engaging in self-care and glycaemic control among patients with type 2 diabetes mellitus (T2DM). DESIGN: A cross-sectional study. SETTING: 2 tertiary-level hospitals and 2 secondary-level hospitals in Japan. PARTICIPANTS: A consecutive sample of 209 outpatients with T2DM. Inclusion criteria were as follows: presence of T2DM, age 20–74 years, no diagnosis of dementia and/or psychosis, and no need for urgent medical procedures. OUTCOME MEASURES: Study measures included a self-administered questionnaire to assess the Rosenberg Self-Esteem Scale (SES), the 3 subscales of 36-question Short Form Health Survey (SF-36; Social Function, Role Physical, Role Emotional), Self-Stigma Scale and Patient Activation Measure (PAM-13). Glycated haemoglobin was obtained from same day blood work. In our previous qualitative study, we found that psychological and behavioural patterns of stigma varied according to patients' levels of illness-related self-esteem as well as attitudes towards social participation. For quantitative consistency, we used the SES scale to measure self-esteem and the SF-36 subscales to measure social participation. We then divided participants into 4 groups by exhibited psychological and behavioural patterns: group A (high SES/high SF-36), group B (high SES/low SF-36), group C (low SES/high SF-36) and group D (low SES/low SF-36). RESULTS: Using analysis of covariance after controlling for age and sex, there was a significant difference in self-stigma levels between the four groups (F[3203]=15.70, p<0.001). We observed the highest mean self-stigma levels in group D. Group D also had significantly lower PAM-13 scores than those of groups A (p<0.001) and B (p=0.02). CONCLUSIONS: The psychological and behavioural pattern of group D was found to be associated with higher levels of self-stigma and poorer patient activation for self-care.